2013
DOI: 10.1002/jcb.24657
|View full text |Cite
|
Sign up to set email alerts
|

MADD Is a Downstream Target of PTEN in Triggering Apoptosis

Abstract: Mitogen-activated kinase activating death domain containing protein (MADD) is abundantly expressed in cancer cells and necessary for maintaining cancer cell survival. However, this survival function of MADD is dependent upon its phosphorylation by protein kinase B (Akt). The tumour suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10) is a lipid phosphatase that negatively regulates the phosphatidylinositol 3-kinase (PI3K)-Akt signalling pathway. The downstream targets of PTEN in triggering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…While Thr366 phosphorylation is thought to lead to PTEN destabilization [35], the contribution of Ser-362 phosphorylation to PTEN function is not known. Given that this tumor suppressor is known to contribute to both intrinsic survival pathways [36] and the extrinsic cell death pathways [37,38], the overall effect of GSK-3βi on therapeutic apoptosis in B-lymphoid malignancies would have been difficult to predict with certainty. The fact that one of its key targets Myc has manifold effects on tumor cell survival only adds to the complexity of this system.…”
Section: Gsk-3β and Therapeutic Apoptosismentioning
confidence: 99%
“…While Thr366 phosphorylation is thought to lead to PTEN destabilization [35], the contribution of Ser-362 phosphorylation to PTEN function is not known. Given that this tumor suppressor is known to contribute to both intrinsic survival pathways [36] and the extrinsic cell death pathways [37,38], the overall effect of GSK-3βi on therapeutic apoptosis in B-lymphoid malignancies would have been difficult to predict with certainty. The fact that one of its key targets Myc has manifold effects on tumor cell survival only adds to the complexity of this system.…”
Section: Gsk-3β and Therapeutic Apoptosismentioning
confidence: 99%
“… 24 Meanwhile, MADD is a downstream target of PTEN in triggering apoptosis. 25 Further investigations revealed that miR-1197 overexpression-caused decreases in cell proliferation, migration and invasion were significantly prevented by overexpression of MADD. The results indicated that miR-1197 exerted its tumor suppresser effects by targeting MADD in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This would be most prevalent in older subjects, which had highly elevated hyperplasia rates. Second, given that Pten regulates apoptosis 37 , HFD could concurrently deregulate hyperplasia and apoptosis by deregulating Pten activity. Finally, gestational diet could deregulate both Pten/Akt-driven proliferation and another independent pathway, leading to an upshift in apoptosis.…”
Section: Discussionmentioning
confidence: 99%